Shake! - Jussi & The Boys; Raittinen, Jussi; Lupari, Eero; Metsberg, Jari; Ryynänen, Antero; Syrjänen, Panu; Tokazier, Hillel; Boys (Ding Dong Song, 2002)
15 kappaletta.
Keywords: Jussi & The Boys : albumit